Dopamine D2 receptor gene Taq 1A polymorphism: genetic architecture in Indian population and comparison to global populations - Chaudhary, Amrita; Kumar, Pradeep; Sharma, Bechan; Rai, Vandana (Frontiers in Genetics, 2025)
ObjectiveThe Dopamine receptor D2 (DRD2) gene has been investigated as a candidate gene in several psychiatric and neurological disorders involving dopaminergic systems. Multiple polymorphisms have been reported in the DRD2 gene, where the DRD2 Taq1A is most widely studied and is reported to contribute to the development of several diseases/disorders. The objective was to study the DRD2 Taq1A polymorphism in the Indian population and compare it with the reported global frequency.MethodsThe DRD2 Taq1A polymorphism was genotyped using PCR-RFLP from 400 unrelated human blood samples. In addition, a literature search on the DRD2 Taq1A polymorphism has also been conducted from 1990 to 2025. All the data obtained was grouped according to the continent as a unit to get the distribution information of the DRD2 Taq1A genotypes and alleles in healthy populations of all six continents. This was accomplished for the comparison of frequency obtained in this study with the overall geographical distribution of the DRD2 Taq1A allele reported from other parts of the world.ResultsIn the total 400 samples analyzed, the TT genotype and T allele frequencies were 15% and 43%, respectively. Data from 136 studies from different continents were extracted and compared with the present study. The highest T allele frequency was observed in the Asia (0.35), followed by South America (0.33) and the lowest frequencies occur in Europe and Australia (0.19). Pattern of frequencies represented by the Indians is consistent to Asia and close to South America. The result show a high frequency of CT genotype and T allele in the study population, closely resembling the patterns observed in Mexicans. This study highlights the genetic diversity within Indian subpopulations and underscores the need for cautious interpretation of population genetic data.ConclusionThe present study observed a T allele frequency of 43%, comparable with the Asian population. In the comparison study, the T allele frequency in Global, Asian, Indian, and present studies was calculated as 26%, 35%, 33%, and 43%, respectively. This geographical gradient is clinically important in determination of the risk assessment which might be included in prevention strategies for psychiatric disorders.